Effect of Solid to Solvent Ratio and Extraction Time on Yield, Phytochemical Content and Physicochemical of Amla (Phyllanthus emblica) Seed Oil Extracted using Hexane - Mauliza, Nadia Putri; Suriaini, Nanda; Rosnelly, Cut Meurah; Satriana, Satriana; Supardan, Muhammad Dani (Jurnal Rekayasa Kimia & Lingkungan, 2022)
Amla (Phyllanthus emblica) seeds have only been disposed of as waste and have not been utilized optimally. Utilizing the seeds to produce oil has been regarded as a promising approach for reducing solid wastes and producing value-added products. This study evaluated the effect of solid to solvent ratio and extraction time on yield, phytochemical content and physicochemical of oil extracted from amla seed using hexane as a solvent. The amla seed oil was extracted through the solid-liquid process at different solid to solvent ratios (1:20, 1:25 and 1:30 g/mL) and extraction times (30, 60, 90 and 120 minutes). The highest yield found was 10.97% at a solid to solvent ratio of 1:30 (g/mL) and an extraction time of 120 minutes. The highest concentrations of phenolic compounds and flavonoids were 66.12 mg GAE/g and 95.70 mg QE/g respectively, obtained at a solid to solvent ratio of 1:25 (g/mL) and extraction time of 120 minutes. Physicochemical analysis (pH, density, acid number, free fatty acid, and peroxide number) showed that the quality of extracted oil was better than what the previous study reported. In the amla seed oil, the content of unsaturated fatty acids was higher than saturated fatty acids with linoleate as the main component. These results clarified that solid-liquid extraction method can be used for extracting amla seed oil and also indicated that amla seed oil can be used as an ingredient in health-related industry products.